Parâmetros Técnicos para o Aproveitamento Ornamental dos Granitóides Jaguari e Santa Rita, Região de Ibaré, Oeste do Escudo Sul-Rio-Grandense - RENNER, LEONARDO CARDOSO; PULZ, GÊNOVA MARIA (Pesquisas em Geociências, 2005)
<!-- .p { text-align: justify; } --> The Jaguari and Santa Rita Intrusive suites crop out in the Ibaré region, Southwestern of Sul-rio-grandense Shield, around 340 km from Porto Alegre, Rio Grande do Sul State. These stratigraphic units contain granites of Brasiliano Cycle, which are research to aim ornamental stones. The studied granites occur in boulder fields and pavements. The granulation, colour and paragenesis of the studied rocks were considered as criteria to distinguish petrographic facies to ornamental applications. Petrographic data combined with technological assays (absorption, apparent porosity, density, sound velocity, resistance to bending, uniaxial compressive strength, impact strength and Amsler abrasion) of red sienogranite facies of Jaguari Intrusive Suite, as well as the pink and grey monzogranite facies of Santa Rita Intrusive Suite indicate that these rocks are adequate to use in façades facing and trim, decorative and engineering purpose (stone flooring and structural performance).